2022
DOI: 10.1002/batt.202200436
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the Electrolyte Polarity to Address the Dissolution Issue of Organic Electrode

Abstract: Small organic molecules with carbonyl active site are a prominent member in the family of organic electrode material, due to the reversible reaction and more tunable electrochemical property. However, the dissolution loss is the biggest obstacle in its application. In this work, we tried to address the dissolution issue of 5,7,12,14-pentacenetetrone (PT), a typical quinone-based organic electrode. Highly concentrated electrolyte of 5 M LiTFSI DME was used and it significantly reduced the dissolution and well m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To circumvent the dissolution problem, we employed a highly concentrated electrolyte. In a high-salt-concentration electrolyte solution, fewer solvent molecules are capable of interacting with the active materials in the electrode, thus reducing its dissolution . Indeed, when we immersed the NDI-2Vi electrode in a DOL/DME (1:1) electrolyte solution containing 6 M LiTFSI, it was observed that the dissolution of NDI-2Vi was significantly retarded.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To circumvent the dissolution problem, we employed a highly concentrated electrolyte. In a high-salt-concentration electrolyte solution, fewer solvent molecules are capable of interacting with the active materials in the electrode, thus reducing its dissolution . Indeed, when we immersed the NDI-2Vi electrode in a DOL/DME (1:1) electrolyte solution containing 6 M LiTFSI, it was observed that the dissolution of NDI-2Vi was significantly retarded.…”
Section: Resultsmentioning
confidence: 99%
“…The initial discharge capacity delivered by the NDI-2Vi cathode in the 6 M LiTFSI electrolyte was measured to be 110.7 mA h g –1 , corresponding to 70% of the theoretical capacity (Figure b). The lower capacity utilization in the highly concentrated electrolyte is due to the low ion conductivity caused by high viscosity of the electrolyte . Then, the discharge capacity suddenly dropped to 92.2 mA h g –1 at the second cycle; however, the NDI-2Vi electrode exhibited stable cycle stability thereafter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar effect has already been observed in lithium organic batteries, where the use of concentrated electrolytes suppressed the dissolution of small organic cathode materials. 28,29 The cycling stability of small organic cathode materials is inuenced by the depth of discharge, which inuences the This journal is © The Royal Society of Chemistry 2023 amount of active material dissolution. 22 To improve the cycling stability different cutoff voltages of 0.8 V, 0.6 V, 0.4 V, and 0.25 V were tested.…”
Section: Battery Performancementioning
confidence: 99%